Complementary efficacy and molecular insights of Polygonati rhizoma polysaccharide for glycemic and lipid abnormalities in type 2 diabetes mellitus: a comprehensive review - Ma, Shichao; Xu, Lu; Hou, Yadi; Zhang, Wenjing; Cui, Yongxia; Chen, Suiqing (Frontiers in Endocrinology, 2025)
BackgroundT2DM is a global health challenge characterized by insulin resistance and impaired glucose metabolism. Natural products, such as polysaccharides from medicinal plants, are increasingly explored for their potential in managing T2DM with fewer side effects compared to conventional drugs.AimThis review aims to comprehensively evaluate the effects of Polygonati Rhizoma Polysaccharide (PRP) on glucose and lipid metabolism in T2DM and elucidate its underlying molecular mechanisms.IntroductionIn recent years, numerous scientific studies have demonstrated that Polygonati Rhizoma Polysaccharide (PRP) exerts beneficial effects on type 2 diabetes mellitus (T2DM), enhancing both glucose and lipid metabolism. This article provides a comprehensive review of the impact of PRP on T2DM influencing glucose and lipid metabolism and elucidates the underlying molecular mechanisms.MethodsA comprehensive literature search was conducted across electronic databases including PubMed, Web of Science, Wanfang Database, and China National Knowledge Infrastructure (CNKI). The search encompassed publications from June 2010 to June 2025, representing a 15-year period. Titles and abstracts were systematically screened for relevance, after which full-text articles meeting the inclusion criteria within this timeframe were selected for analysis.DiscussionCurrent evidence indicates that PRP can ameliorate T2DM alongside improving glucose and lipid profiles; this effect is predominantly linked to its modulation of the PI3K/AKT signaling pathway. Furthermore, its lipid-lowering properties are associated with regulation of gut microbiota, enhancement of intestinal barrier function, promotion of short-chain fatty acids (SCFAs) production, activation of G Protein-Coupled Receptors 41 and 43 (GPCR41 and 43), as well as inhibition of the TLR4/MyD88/NF-κB signaling cascade.ConclusionPolygonati Rhizoma Polysaccharide can obviously improve the hyperglycemia and hyperlipidemia caused by T2DM, and has certain anti-inflammatory and antioxidant effects.